Phospholipid Arachidonic Acid Remodeling During Phagocytosis in Mouse Peritoneal Macrophages - Luis Gil-de-Gómez; Patricia Monge; Juan P. Rodríguez; Alma M. Astudillo; María A. Balboa; Jesús Balsinde (Biomedicines, 2020)
Macrophages contain large amounts of arachidonic acid (AA), which distributes differentially across membrane phospholipids. This is largely due to the action of coenzyme A-independent transacylase (CoA-IT), which transfers the AA primarily from diacyl choline-containing phospholipids to ethanolamine-containing phospholipids. In this work we have comparatively analyzed glycerophospholipid changes leading to AA mobilization in mouse peritoneal macrophages responding to either zymosan or serum-opsonized zymosan (OpZ). These two phagocytic stimuli promote the cytosolic phospholipase A2-dependent mobilization of AA by activating distinct surface receptors. Application of mass spectrometry-based lipid profiling to identify changes in AA-containing phospholipids during macrophage exposure to both stimuli revealed significant decreases in the levels of all major choline phospholipid molecular species and a major phosphatidylinositol species. Importantly, while no changes in ethanolamine phospholipid species were detected on stimulation with zymosan, significant decreases in these species were observed when OpZ was used. Analyses of CoA-IT-mediated AA remodeling revealed that the process occurred faster in the zymosan-stimulated cells compared with OpZ-stimulated cells. Pharmacological inhibition of CoA-IT strongly blunted AA release in response to zymosan but had only a moderate effect on the OpZ-mediated response. These results suggest a hitherto undescribed receptor-dependent role for CoA-independent AA remodeling reactions in modulating the eicosanoid biosynthetic response of macrophages. Our data help define novel targets within the AA remodeling pathway with potential use to control lipid mediator formation